Тhe production of porous gallium phosphide films and the investigation of physical properties - Sarsembek, S.S.; Mussabek, G.K.; Dikhanbaev K.К.; Ermukhamed, D.; Baiganatova, Sh.B.; Amirkhanova, G.A. (Recent Contributions to Physics, 2018)
Among a wide class of semiconductor materials, AIIIBV compounds are widely used in the production of efficient electronic and photonic devices. It is known that for materials used in modern semiconductor electronics, nanoscale materials are considered to be the most relevant and nanostructured porous materials are particularly noteworthy. Recently, the interest of researchers and developers of new light-emitting structures and instruments is attracted by porous gallium phosphide, the crystal modification of which is used in the production of various predominantly green light-emitting devices. Obtaining of homogeneous and stable nanoporous structures of gallium phosphide is one of the most difficult technological problems, for the solution of which many different methods have been proposed. Among proposed methods, the electrochemical etching method proved to be the most effective to achieve positive results. Present paper is devoted to the survey of obtaining of porous gallium layers by means of electrochemical etching and of basic scientific and technical achievements in the field of research and application of its physical properties. The article describes the general technology for the production of porous gallium phosphide by electrochemical etching, discusses the technological features of controlling the etching process, discusses the influence of technological conditions for obtaining physical properties of the resulting material, and gives examples of the application of the material.